Clinical Outcome of Cloacal Exstrophy, Current Status, and a Change in Surgical Management - Vliet, Rob van; Roelofs, Luc A. J.; Rassouli-Kirchmeier, Roxana; de Gier, Robert P. E.; Claahsen-van der Grinten, Hedi L.; Verhaak, Chris; Hosman, Allard J.; Beerendonk, Catharina C. M.; van Lindert, Erik J.; Willemsen, Michel A. A. P.; Wijnen, Marc H. W. A.; Feitz, Wout F. J.; de Blaauw, Ivo (European Journal of Pediatric Surgery, 2015)
Introduction Cloacal exstrophy is a complex and rare congenital malformation. Because of improvements in medicine, operative techniques, and perioperative management the survival rates are now approaching 100%. Currently, treatment is focused on improving quality of life. Since 1974, we encountered 20 patients with cloacal exstrophy in our hospital. The aim of this study is to evaluate our clinical experience and outcome during the last 39 years.Patients and Methods A retrospective study of the medical records was performed. We evaluated anatomical status, phenotype and genotype at birth, subsequent surgical treatment and current gastrointestinal, urinary, spinal, genital, and gender status and outcome.Results The records of all 20 patients who were treated in our center were included in this study. Of the 20 patients, 18 were primary patients, 2 referred. Six patients died within the first year of life. Median age of the surviving 14 patients was 25 years (range, 4–39 years) at time of evaluation. At the last follow-up, 11 patients had an endileostomy or endcolostomy. Three patients had a pull-through; two of them were continent for feces. Two patients were continent for urine; one with a sinus urogenitalis and one after urethra reconstruction. Eleven patients are incontinent; six of them had an incontinent urinary deviation (Bricker deviation). Of the other five incontinent patients, two had a urethral reconstruction, one vesicovaginal anastomosis, one perineotomy, and one epispadias bladder. Urinary continence was unknown in one patient. Of the surviving patients, nine have 46 XY karyotype and five 46 XX karyotype. Initially, six XY patients underwent external genital reconstruction with reassignment to female gender; however, one died postoperatively. One declared to feel like a man at age of 15 years. Remaining four XY patients underwent male external genital reconstruction. All XX patients underwent vagina or vulva reconstruction, except for one who still has aplasia vaginae. All patients were born with varying types of spinal dysraphism.Discussion Despite medical efforts and development in treatment and support, satisfaction in outcome of cloacal exstrophy remains a challenge. Although reconstruction may be very difficult, male genital reconstruction in 46 XY patients has been given preference for more than a decade. A specialized multidisciplinary team should provide lifelong colorectal, urological, sexual, and psychosocial support to these patients, taking into account their age and phase of life.
Keywords: cloacal exstrophy; OEIS-complex; gender reassignment; vesicointestinal fissure; outcome